Can urban agglomeration bring "1 + 1 > 2Effect"? A perspective of land resource carrying capacity. (June 2022) - Shen, Liyin; Cheng, Guangyu; Du, Xiaoyun; Meng, Conghui; Ren, Yitian; Wang, Jinhuan
Abstract: Encountered with scarce land resources in contemporary time, mankind has been seeking for solutions to improve land resource carrying capacity to sustain urban development. The development pattern of urban agglomeration has been well received globally in recent years as an alternative strategy to improve land resource carrying capacity. Many countries have been committing to urban agglomeration development plans with the expectations of gaining "1 + 1 > 2Effect" from utilizing land resources between cities. However, few existing studies have conducted in examining whether and to what extent "1 + 1 > 2Effect" on land resource carrying capacity can be gained through implementing urban agglomeration strategy. This paper presents an investigation on whether urban agglomeration can bring "1 + 1 > 2Effect" to cities from the specific perspective of land resource carrying capacity. An analysis model is developed for assisting the investigation by using Difference-in-Differences method. The Pearl River Delta region in China is selected as a case urban agglomeration to assist empirical research. The results from this study suggest that urban agglomeration development plan can bring limited "1 + 1 > 2Effect" from the perspective of land resource carrying capacity and contributes to the improvement of economic performance between cities within the urban agglomeration. The findings nevertheless also indicate that land resource carrying capacity cannot be improved exclusively by implementing urban agglomeration development plan. Critical issues are addressed for more attention during implementing urban agglomeration strategies. The paper provides valuable references for policymakers to understand the effects of urban agglomeration on land use and sheds light on the importance of researching on the impacts of urban agglomeration. Highlights: ● Urban agglomeration is expected to achieve more benefits than the sum of fragmentary cities can achieve. ● "1 + 1 > 2Effect" is used as a measurement to examine the effect of an urban agglomeration. ● Urban agglomeration development plan brings limited "1 + 1 > 2Effect" on improving land resource carrying capacity. ● Urban agglomeration should not be considered as a universal instrument to improve land resource carrying capacity.